Direct prediction of bidirectional reflectance by dense particulate deposits. (February 2019) - Ramezanpour, Bahareh; Mackowski, Daniel W.
Highlights: PWPP results depart from radiative transfer as particle concentration increases. Increasing volume fraction shifts polarimetric radiation towards backwards direction. The plane wave plane parallel (PWPP) method can predict opposition effects. Coherent-backscattering height strongly depends on size parameter/volume fraction. Polarization opposition depth decreases with concentration for a = 1; opposite for a = 2. Abstract: To observe and study the effects of the volume packing density on polarimetric scattering by deposited particulate materials, a comparison is made between the vector radiative transport equation (VRTE) and the plane wave plane parallel (PWPP) models for the polarized bidirectional reflectance and transmittance from plane parallel layers of randomly distributed, wavelength–sized particles. Calculations have been performed on ice and mineral materials with refractive indices of m = 1.31 and m = 1.5 + 0.01 i respectively. In these simulations, particle volume fraction ranges from around 0.05–0.3 for deposits consisting of spherical particles with size parameters of one and two. It is found that the PWPP model results converge to those predicted by the VRTE at small ( ∼ 5% or less) particle volume fractions. At higher volume fractions, the difference between the PWPP and VRTE results depends strongly on the particle size and refractive index, yet not so much on the optical thickness (equivalently, volume of particles per unit area of layer). PWPP simulation results of coherent backscattering effects – brightness opposition and polarization opposition effects – for ice and mineral particles are also represented. Their dependency on the particle volume fraction and particle size has been discussed.